KEBEBASAN KRISTEN DI ERA DIGITAL: PRINSIP ETIS-TEOLOGIS BERDASARKAN 1 KORINTUS 6:12 - Vinsensia Nitamawar Tafonao; Moses Wibowo (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Jakarta, 2024)
The development of technology has a positive impact, making it easier for humans to do their work. However, in addition to having a positive impact, technology also hurts its users. The rise of cybersex on social media is very dangerous because it is detrimental to many people including Christians. Cybersex can cause sexual urges because of sex offerings on the internet. There are several cybersex practices, including prostitution, harassment, and pornography that show declining moral behaviour in this generation in the digital era. Efforts are needed to tackle the spread of cybersex and its negative impact on Christian life. That freedom does not negate the responsibility of being a believer. This article will conduct a biblical study of 1 Corinthians 6:12 and relate it to